An anatomy of bonding in the dyadic system - Lynch, Barbara J. (Journal of Couples Therapy, 1991)
Bonding is an essential factor in the establishment and maintenance of an intimate committed relationship. Dissecting elements of bonding leads to an understanding of the internal structure of the marriage. Attraction and bonding are different and equally vital in turning initial romance into enduring intimacy. The process of attraction based on projections developing into an enduring bond between peers merges relationship purpose and a rationale for emotional involvement. This occurs when attention is accorded to each of the factors of bonding; ego-equality, respect, interdependence and reality grounding. In therapy, a couple’s bonding can be assessed through the isomorphic qualities actualized in the therapeutic joining process. Discussions includes over bonded and under bonded couples, their presenting problems, and a treatment focus for each condition. © 1991 Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: pop00118 tex.type: [object Object]
Keywords: dept.mft